UPAYA MENINGKATKAN KESEJAHTERAAN MASYARAKAT MELALUI PROGRAM PENGEMBANGAN WISATA TAMAN KREATIF DI KELURAHAN PIPITAN KECAMATAN WALANTAKA KOTA SERANG - Raden Irna Afriani; Listiawati Listiawati; Ahmad Mukhlis; Ihwan Satria Lesmana; Abdul Bahits; Wahyu Widodo; Muhammad Saleh (Yayasan Education and Social Center, 2022)
Tourism development is currently aimed at sustainable tourism development with development based on the principle of community-based empowerment. One of the villages that developed with these principles is Pipitan Village. Pipitan Creative Park is a new tourist attraction in Kota Serang that has many tourist destinations. Pipitan Creative Park tourism has resources that are abundant enough that it has considerable tourist potential to be developed as a tourist attraction. This place when considered more than potential can be developed as a charming beauty makes tourists more comfortable. In this case, the program implemented is to further develop the Pipitan Creative Park of Walalantaka Subdistrict. In tourism management, there are several aspects of planning, management, supervision and evaluation. But in its implementation, not optimal for this reason, the management of tourism awareness groups (Pokdarwis) is necessary. Human Resource Development, Friendly local population and Artisan community training. These methods are used to improve the economy of the community by organizing events involving the community around tourist attractions, maintenance of garbage tubs and cooperation programs with third parties. The positive impact on Creative Park attractions is the opening of jobs, increasing community income, the use of tourist facilities in the local community.